Perception of User Experience on Youtube With Regard to Advertising : ‘A Moroccan Exploratory Study - Achraf DADOUH; Zineb LAHMIDI (Communications of International Proceedings, 2024)
YouTube remains one of the most important platforms on the Internet, given its importance in the daily lives of users and in advertisers' promotional strategies. In fact, while this video-sharing platform attracts billions of users around the world, it also captivates advertisers seeking to effectively reach the target audiences of their campaigns. This creates a situation of omnipresence of ads on the platform, which prompts controversy regarding the user experience. In previous research, the perception of users regarding ads on YouTube has widely been studied. However, the impacts of ads on the user experience of YouTube have rarely been addressed so far. For this reason, we chose to carry out an exploratory study with an aim to concretely elucidate the concept of user experience in this case. To do so, we focused on how ads affect the perception of Moroccans regarding the user experience on YouTube. The study, which was conducted through interviews with two focus groups of Moroccan university students and analyzed using NVivo 14, showed that four main factors are at the origin of this perception: irritation, avoidance, entertainment and viewing time. Such insights should help us determine more relevant variables for future research, targeting a larger population.
Keywords: User experience; YouTube; advertising; user perception.